2008
DOI: 10.1186/1471-2164-9-363
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of RUNX1 downstream pathways and target genes

Abstract: Background: The RUNX1 transcription factor gene is frequently mutated in sporadic myeloid and lymphoid leukemia through translocation, point mutation or amplification. It is also responsible for a familial platelet disorder with predisposition to acute myeloid leukemia (FPD-AML). The disruption of the largely unknown biological pathways controlled by RUNX1 is likely to be responsible for the development of leukemia. We have used multiple microarray platforms and bioinformatic techniques to help identify these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 60 publications
2
105
0
Order By: Relevance
“…Together these proteins form a transcription factor complex that is widely expressed in various hematopoietic lineages and regulates the expression of several critical genes. 3 Since the identification of RUNX1 as the causative gene in FPD/AML, 2 only 25 mutation-positive families have been reported in the literature, which suggests that FPD/AML is a relatively rare disorder. An additional explanation may be that this disorder is underdiagnosed, as was recently suggested by Owen et al, 1 who identified RUNX1 mutations in 50% (5/10) of families with more than one first degree relative with myelodysplastic syndrome (MDS) and/or AML.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Together these proteins form a transcription factor complex that is widely expressed in various hematopoietic lineages and regulates the expression of several critical genes. 3 Since the identification of RUNX1 as the causative gene in FPD/AML, 2 only 25 mutation-positive families have been reported in the literature, which suggests that FPD/AML is a relatively rare disorder. An additional explanation may be that this disorder is underdiagnosed, as was recently suggested by Owen et al, 1 who identified RUNX1 mutations in 50% (5/10) of families with more than one first degree relative with myelodysplastic syndrome (MDS) and/or AML.…”
mentioning
confidence: 99%
“…1,2 Chronic lymphocytic leukaemia (CLL) is a B-cell malignancy with increased incidence among the elderly. The disease is due to an imbalance between cell death and proliferation resulting in an accumulation of malignant cells in the bone marrow and peripheral blood (reviewed in Van Bockstaele et al 3 ). Clinically, the disease varies from indolent, which may progress to/or appear at diagnostic as an aggressive incurable form.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, conditional deletion of Runx1 in DN2 thymocytes resulted in a partial block in DN3 to DN4 differentiation and impaired DN4 proliferation [284]. A gene expression microarray performed on Runx1-null embryos suggested that Runx1 targets also include genes involved in cell motility, cell proliferation, and cytoskeletal organization according to a biological pathway analysis [313]. Since we also detect altered expression of genes involved in similar …”
Section: Btg1mentioning
confidence: 98%